2017
DOI: 10.1105/tpc.16.00718
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Transposable Elements Circumvent Identity-Based Silencing, Permitting the Dissection of Expression-Dependent Silencing

Abstract: ORCID ID: 0000-0001-9582-3533 (R.K.S.)The propagation of epigenetic marks has received a great deal of attention, yet the initiation of epigenetic silencing of a new transgene, virus, or transposable element (TE) remains enigmatic. The overlapping and simultaneous function of multiple silencing mechanisms has obscured this area of investigation. Here, we revealed two broad mechanisms that can initiate silencing independently: identity-based and expression-dependent silencing. We found that identity-based silen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 66 publications
4
61
0
Order By: Relevance
“…The ATCOPIA93-LTR::GUS fusion was consistently found to be unmethylated in various transgenic lines in the wild-type Col-0 background, concordant with LTR::GUS reactivation in response to PtoΔ28E. This lack of de novo methylation upon transformation may be explained by weak LTR transcriptional activity in untreated plants, thus preventing expression-dependent RNA-directed DNA methylation (Fultz & Slotkin, 2017) and/or by low levels of CHH methylation/siRNAs at ATCOPIA93 (Fig 1A; Mirouze Marí-Ordóñ ez et al, 2013), thus preventing identity-based silencing in trans (Fultz & Slotkin, 2017). Similarly, in wild-type plants, the ATCOPIA93-soloLTRs appear usually to be constitutively unmethylated ( Fig EV5A), in particular the soloLTR-5 described in detail here.…”
Section: Discussionmentioning
confidence: 69%
“…The ATCOPIA93-LTR::GUS fusion was consistently found to be unmethylated in various transgenic lines in the wild-type Col-0 background, concordant with LTR::GUS reactivation in response to PtoΔ28E. This lack of de novo methylation upon transformation may be explained by weak LTR transcriptional activity in untreated plants, thus preventing expression-dependent RNA-directed DNA methylation (Fultz & Slotkin, 2017) and/or by low levels of CHH methylation/siRNAs at ATCOPIA93 (Fig 1A; Mirouze Marí-Ordóñ ez et al, 2013), thus preventing identity-based silencing in trans (Fultz & Slotkin, 2017). Similarly, in wild-type plants, the ATCOPIA93-soloLTRs appear usually to be constitutively unmethylated ( Fig EV5A), in particular the soloLTR-5 described in detail here.…”
Section: Discussionmentioning
confidence: 69%
“…4d). Experimental data have demonstrated that silencing of active TEs occurs quickly, within a few host generations (Teixeira et al, 2009;Mari-Ordonez et al, 2013;Fultz & Slotkin, 2017). It is thus very likely that old Gypsy elements have been silenced at least once and then reactivated more recently.…”
Section: Researchmentioning
confidence: 99%
“…Therefore, Pol IV's overall function in plant biology is to generate the siRNAs necessary to reinforce heterochromatic marks and maintain euchromatin/heterochromatin boundaries [10]. A secondary role is to generate an siRNA defense against any new or active TEs that share sequence homology [11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Pol IV's overall function in plant biology is to generate the siRNAs necessary to reinforce heterochromatic marks and maintain euchromatin/heterochromatin boundaries [10]. A secondary role is to generate an siRNA defense against any new or active TEs that share sequence homology [11].Pollen is the male gametophytic generation of flowering plants, and contains two sperm cell gametes encapsulated in a larger vegetative cell, which directs the delivery of the sperm cells upon pollination. Pollen has a known broad activation of TE expression resulting in steadystate TE mRNAs, which occurs from the nucleus of the pollen vegetative cell [12,13].…”
mentioning
confidence: 99%